Neissabourian Houses - ظفار قحطان عبد الستار (College of Education for Women, 2019)
Neissabour city becomes one of great and important cities after the real interaction that happens between Islamic Arabs and orginal population of City in mental social and economic points Nessabour starts to accept the cultural development from leadership of arabs in public life that make it becomes the greatest city of Islamic orient and important city in movement of scientific cultural construction . the ability and position appears when it becomes center of Kharassan staten . that the prince Abdulah Abn Taher takes it as reign location of Taherian Emirat at (213 A.H) This city takes to develop of Arabic and Islamic development of many scientists jurists thinkers and authors . that expands field in front of the people to appear scientific and mental abilities . but others establish the scientific houses by Neissaboraan scientific activity that create and excel like the Rawanerian and Micalian houses . that to be shown in research by show the important famous scientists and jurists by favor of their wish to gain the science and knowledge . They win interest and respect of khalifas of the Arabic Islamic state for them and their scientific houses . by give them administrative ranks that they excel by this ranks . the leaders of muslims give the scientists many gifts to benefit from their scientific and administaive experiences that is postion of trust from Islamic Leaders . then the result is valuab heritage of many sciences.